Comparison between diffuse and partial involvement of thoracic lymph nodes on the outcome of sarcoidosis patients - Persky, Ofir; Kassirer, Michael; Ostrovsky, Daniel; Osyntsov, Lydia; Raviv, Yael (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Background and aim: Sarcoidosis is a systemic disease of unknown etiology with diverse clinical manifestations. Disease may resolve spontaneously or require immunosuppression to control progression. Currently, there is no predictive model to direct treatment, and management is guided by symptoms and functional impairment. This study examines the association between biopsy features and prognosis. Methods: This is a retrospective population-based cohort study. New cases of biopsy-proven sarcoidosis were divided into two groups: those with diffuse thoracic lymph nodes (TLN) involvement, versus partial TLN involvement (Defined as Non-necrotizing granuloma (NNG) found in some but not all sampled TLN). We compared outcomes one year after diagnosis. We assessed the need for immunosuppression, the number of hospitalizations, and lung function deterioration. Results: 77 cases were included in the final analysis. 48.1% demonstrated extensive TLN involvement, and 51.9% demonstrated partial or non-involvement of sampled TLN. The partial positive group had a more aggressive disease, reflected by a significantly higher need for steroid therapy in the first year after diagnosis (45.0% vs. 18.9% p=0.015). The number of hospitalizations and lung functions were not significantly different between groups. Conclusions: Our findings demonstrate a significantly increased need for steroidal therapy among sarcoidosis patients with a partial positivity of TLN. These findings suggest that the degree of TLN involvement can help predict worse outcome and guide therapeutic decisions.